RFID(Radio Frequency Identification) Localization and Application (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
RFID opens new frontiers in society and industry, where a wide range of RFID-enabled applications are emerging in smart industries, logistics, smart cities, smart healthcare, safety, and security, among others. RFID involves multidisciplinary areas of research and development, encompassing a broad spectrum of science and engineering expertise. The following book is a reprint of the Special Issue “RFID (Radio Frequency Identification) Localization and Application” that was published in the journal Applied Sciences, highlighting significant strides and emerging trends within the dynamic field of RFID technology. The ten papers featured in this Special Issue collectively provide a comprehensive overview of the current state of RFID research, spanning diverse applications and theoretical advancements that push the boundaries of what is possible with this transformative technology.